2014
DOI: 10.1039/c4ra03969f
|View full text |Cite
|
Sign up to set email alerts
|

Polyiminofluorene with conjugated benzimidazolylpyridine substituent groups: optical properties, ionochromism and coordinative self-assembly into electrochromic films

Abstract: A new polyiminofluorene with conjugated bis(methylbenzimidazolyl)pyridine ligands in the side chain has been synthesized. Ionochromism of the polymer and electrochromic behaviour after coordinative layer-by-layer assembly into ultrathin films are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Using this approach electrochromic and photoluminescent films were recently described by our group . It was shown that a structural variation of polymer, metal ions, and counterions can be used to vary and optimize the functional properties of the films …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this approach electrochromic and photoluminescent films were recently described by our group . It was shown that a structural variation of polymer, metal ions, and counterions can be used to vary and optimize the functional properties of the films …”
Section: Introductionmentioning
confidence: 99%
“…As a continuation of our previous studies on coordination polymer films and on the transport of ions and molecules across polyelectrolyte multilayer films, we now became interested in the study of materials transport across coordination polymer films. Motivation for the present work also came from the generally growing interest in metallopolymers, metallo‐supramolecular polymers, and metal organic frameworks and their use as active materials in membrane applications .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] The absorption wavelength of transition metal complexes signicantly depends on the redox state of their building blocks and their properties can be modied by changing the ligands or metal ions. 15 So far, mainly transition metal complexes with oligopyridines or phthalocyanines were examined as electrochromic materials, while electrochromic properties of transition metal complexes with hydrazones have not been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…S1 †). 18,19 Subsequently, this ligand was coupled to dodecanoic acid and bis-carboxylic acid functionalised telechelic poly(ethylene-co- † Electronic supplementary information (ESI) available: A comprehensive account of all experimental details, including synthetic procedures, analytical data, and NMR spectra of all novel compounds is provided. See…”
mentioning
confidence: 99%